PENINGKATAN KEMAMPUAN GURU IPS SMP WILAYAH BINAAN KOTA SEMARANG DALAM MENGEMBANGKAN INDIKATOR DAN INSTRUMEN PENILAIAN MELALUI WORKSHOP DENGAN PERTEMUAN INDIVIDUAL PADA SEMESTER 2 TAHUN PELAJARAN 2014/2015 - Mulyati, Roch (Jurnal Penelitian Pendidikan, 2016)
The research problem is the minimum ability of social studies teachers to develop the indicators of competencies and assessment instruments achievement. This study aims to improve the ability of social studies teachers to develop the indicators of achievement of competencies and assessment instruments through workshops and individual meetings.Determining the teachersâability to develop the competencies achievement indicators,indicator scorecards were used which contains 8 aspects, whereas to determine the ability to develop assessment study instruments,the card consists of three aspects which contains 11sub aspectswere used.Workshops with individual meetings were taken to improve the teachersâability. Workshop selected as an activity that integrates theory and practice as well as to meet the characteristics of adult learning, while the individual meeting were used to solve the problem of an individual nature and eliminate the psychological barriers of teachers who feel embarrassed to revealed problems in the workshop forum.Before the action was carried out, the number of teachers who are able to develop competence achievement indicator is 0%, after cycle 1 = 13.33% and after cycle 2 = 100%. Teachers whowere able to compile an assessment instrument before action is taken, is 6.67%, after the first cycle=60%, after 2 cycles to 100%.